Thematic trends in fact-checking in Brazil’s COVID-19 infodemic: the first year in focus - Azevedo, Nathália Helena; Massi, Luciana [UNESP]; Lima, Guilherme S. (Academia Brasileira de Ciências, 2025)
Fact-checking agencies were pivotal in countering misinformation during the COVID-19 pandemic. We investigated the predominant thematic orientations within Brazilian fact-checking agencies during the pandemic’s initial year. Brazil’s case is relevant because it has a high traffic of false information and was the second country most affected by the pandemic. From Latam Chequea Coronavirus’s database, 838 assertions checked of fact-checking were analysed by automated content analysis, allowing the identification of the thematic incidence through descending hierarchical classification and factorial correspondence analysis. The emerged themes encompassed vaccine, virus origin, social isolation, economic relief, disease mortality, and treatment. Fact-checking agencies assigned varying levels of importance to specific themes, which may reinforce the idea of possible non-neutrality fact-checking journalism. Most categories displayed an irregular publication pattern, indicating they were not part of continuous communicative processes. This research addresses methodological, temporal, and sampling gaps by employing automated analysis, covering the pandemic’s initial year, and utilising a substantial dataset from the global South. The study contributes to the ongoing discourse on fact-checking agencies’ roles and limitations.
Keywords: automated content analysis; COVID-19; fact-checking; fake news; infodemic; disinformation